Receptor for Advanced Glycation End Products Acts as a Fuel to Colorectal Cancer Development - Azizian-Farsani, Fatemeh; Abedpoor, Navid; Hasan Sheikhha, Mohammad; Gure, Ali Osmay; Nasr-Esfahani, Mohammad Hossein; Ghaedi, Kamran (Frontiers in Oncology, 2020)
Receptor for advanced glycation end-products (RAGE) is a multiligand binding and single-pass transmembrane protein taken in diverse chronic inflammatory conditions. RAGE behaves as a pattern recognition receptor, which binds and is engaged in the cellular response to a variety of damage-associated molecular pattern molecules, as well as HMGB1, S100 proteins, and AGEs (advanced glycation end-products). The RAGE activation turns out to a formation of numerous intracellular signaling mechanisms, resulting in the progression and prolongation of colorectal carcinoma (CRC). The RAGE expression correlates well with the survival of colon cancer cells. RAGE is involved in the tumorigenesis, which increases and develops well in the stressed tumor microenvironment. In this review, we summarized downstream signaling cascade activated by the multiligand activation of RAGE, as well as RAGE ligands and their sources, clinical studies, and tumor markers related to RAGE particularly in the inflammatory tumor microenvironment in CRC. Furthermore, the role of RAGE signaling pathway in CRC patients with diabetic mellitus is investigated. RAGE has been reported to drive assorted signaling pathways, including activator protein 1, nuclear factor-κB, signal transducer and activator of transcription 3, SMAD family member 4 (Smad4), mitogen-activated protein kinases, mammalian target of rapamycin, phosphoinositide 3-kinases, reticular activating system, Wnt/β-catenin pathway, and Glycogen synthase kinase 3β, and even microRNAs.